2020
DOI: 10.1007/s00402-020-03594-1
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative damage to surgical gloves during various operations on the musculoskeletal system: a multicenter study

Abstract: Introduction Various orthopedic surgical procedures cause mechanical stress for gloves. In some cases, sharp-edged objects impact on the glove surfaces. The systematic description of lesions is still missing. Methods 2289 gloves from 409 surgeries [primary hip and knee arthroplasties (PA), revisions arthroplasties (RA) and arthroscopic shoulder, hip and knee surgery (AY)] from 3 clinics were examined for lesions using water tightening test according to the European norm EN 455-1. Results Arthroscopies showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…This result is broadly consistent with other studies that have examined surgery time and damage rate [33]. In contrast, especially with mechanically demanding interventions, such as hip or knee endoprostheses or endoprosthetic revision procedures, it was shown that over time, due to accumulation of stress factors, mechanical damage increases in the course of the surgery [14,15]. However, the surgery duration of the majority of surgeries in this study was shorter than the threshold of 90 min, after which a glove exchange is recommended [14].…”
Section: Lesion Rate and Surgery Durationsupporting
confidence: 89%
See 3 more Smart Citations
“…This result is broadly consistent with other studies that have examined surgery time and damage rate [33]. In contrast, especially with mechanically demanding interventions, such as hip or knee endoprostheses or endoprosthetic revision procedures, it was shown that over time, due to accumulation of stress factors, mechanical damage increases in the course of the surgery [14,15]. However, the surgery duration of the majority of surgeries in this study was shorter than the threshold of 90 min, after which a glove exchange is recommended [14].…”
Section: Lesion Rate and Surgery Durationsupporting
confidence: 89%
“…The localization of the damage is consistent with the published data on arthroscopic interventions, where the subordinate hand was also primarily affected [8]. When examining the data on laparoscopy in this study as well as on arthroscopy from a previous study [15], the thumb of the subordinate hand was particularly susceptible to damage in both of the procedures. In these minimally-invasive procedures, instruments and techniques used could be the deciding factor.…”
Section: Tear Locations On Glovessupporting
confidence: 87%
See 2 more Smart Citations
“…Recent studies have shown high rates of glove damage in joint and revision arthroplasty, procedures where gloves are subjected to repetitive mechanical stress during surgery. As a result, the integrity of the gloves is compromised [ 4 , 10 , 11 , 33 ]. However, glove damage was also described in previous studies during much less mechanically demanding operations, such as joint arthroscopies and laparoscopic procedures [ 9 11 , 22 ].…”
Section: Introductionmentioning
confidence: 99%